Islamic Political Identity in West Sumatra within Comparative Muslim Majority Contexts - Frans Pradipta (Politeia: Jurnal Ilmu Politik, 2026)
This study examines the forms and dynamics of Islamic political identity in West Sumatra within a comparative context of other Muslim-majority regions. The findings show that Islamic politics in West Sumatra does not operate through the dominance of Islamic parties, but rather through cultural and moral frameworks shaped by the historical interaction between Minangkabau adat, modernist Islamic education, and religious authority. Using a literature-based method that includes academic articles, books, local regulations, and previous studies, this research reveals that Islamic identity is expressed through symbolic representation, the ties between political elites and ulama networks, and the use of Adat Basandi Syarak, Syarak Basandi Kitabullah values in electoral processes and policy production. Comparatively, this pattern differs from Malaysia, Turkey, and Pakistan, where Islamic politics relies more heavily on state institutions or Islamic party structures. Thus, West Sumatra represents a value-based and adaptive expression of Islamic politics within Indonesia’s democratic system.